A correção com os pares em um contexto de ensino-aprendizagem de Português como língua estrangeira: um estudo com alunos intercambistas na UFG - Rigonato, Lucas Gustavo do Nascimento (2017)
The teaching of Portuguese as a Foreign Language (PLE) has gained prominence in recent years (ALMEIDA FILHO, 2011; FARIA, 2015; FURTOSO, 2015). However, Almeida Filho (2011) calls our attention to the need for research in the area of PLE that re-elaborates the teaching of the language. In this study, I sought to investigate the possible benefits of using an orientation guide during peer review activities in a group of Portuguese as a Foreign Language. Peer review is an activity in which students correct the written text of each other and is premised on the argument that interaction favors learning (FIGUEIREDO, 2006; VYGOTSKY, 1998). For that, the first and second versions of texts written by non-Brazilian exchange students at the Federal University of Goiás (UFG) were contrasted during the first half of 2016. The first language of these students is Spanish. The data were analyzed qualitatively, although some numerical data were used to facilitate the comprehension of the results (NUNAN, 1992). The results demonstrate that peer review activities can be beneficial for language learning as it provides improvement in texts, and students feel benefited by discussing their texts with peers with the aid of an orientation guide.